Mental health and frailty in people with multiple sclerosis: unraveling a complex relationship - Al Worikat, Nida’; Zanotto, Anna; Sosnoff, Jacob J.; Zanotto, Tobia (Frontiers in Psychology, 2024)
People with multiple sclerosis (MS) have up to a 15 times higher risk of being frail compared to agematched individuals without MS. Frailty is a biological syndrome of decreased physiological reserve and resilience that increases the vulnerability to adverse clinical outcomes and leads to a lower quality of life. Recent studies have begun investigating frailty in the context of MS, highlighting several associations between frailty and adverse events, such as falls, and common MS-related symptoms involving the physical health domain, such as walking and sleeping problems. However, there is a critical knowledge gap regarding the relationship between mental health and frailty in people with MS. This mini-review article aimed to shed light on the potential relationships between MS, frailty, and mental health. Despite the dearth of studies on this topic, indirect evidence strongly suggests that the association between frailty and mental health in people with MS is likely bidirectional in nature. Specifically, mental health disorders such as depression and anxiety may be involved in the etiology of frailty in people with MS. However, they could also be exacerbated by the detrimental effects of frailty on overall health. The complex relationship between frailty and mental health in MS underscores the multifaceted challenges people with MS face. Conducting further research to untangle such a relationship is critical to developing early detection and intervention strategies for improving well-being and medical outcomes in people with MS.